Differences in physiological loads and energy consumption of handball referees between periods in handball match - Belcic, I.; Marosevic, A.; Sukreski, M. (World Congress of Performance Analysis of Sport XII, 2018)
The aim of this study was to determine differences in physiological loads and energy consumption of handball referees between halves during handball match. The sample consisted of all 16 referee pairs which counts 32 handball referees who are on list of Croatian Premier handball league (highest handball rank in Croatia). Before the start of testing each participant had signed a voluntary statement for testing and also provided confirmation from medical institution confirming proper state of health. Handball referees measurements were divided into two parts. First part was conducted as laboratory testing, while second part was field test on matches of Premier Croatian handball league. Laboratory measurements started with measuring kinanthropometric measures to identify morphological characteristics. On field tests referees were monitored for physiological loads during matches with a telemetry system for monitoring the heart rate frequency. The average age of referees was 34.29 ± 6,20 years with an average experience of 13 ± 4,99 years in handball refereeing in total (highest level refereeing experience 7.03 ± 4.00 years). Referees had average body height of 184.46 ± 5,78 centimeters and weight of 91,73 ± 10,57 kilograms. Data processing was carried out by statistical package Statistica (version 8). Differences between the two periods of handball matches were tested by t-test for independent samples and the level of significance was set at p < 0.05. T-test for independent samples shows there are no statistically significant differences in maximal and average heart frequency of handball referees during first and second half of handball match as well as there are no statistically significant differences in energy consumption between halves also. Based on the results obtained in this study it can be concluded that handball referees are exposed to high physical and physiological loads during the match with no difference on periods of the match. Due to high influence of referees on final outcome of matches and competitions they need to be at highest possible fitness and concentration level during whole match.